Association between dietary index for gut microbiota and female infertility: a cross-sectional NHANES 2013–2020 - Fu, Yu; Peng, Mengling; Cai, He; Li, Bing; Zhang, Yaoting; Zheng, Yang (Frontiers in Nutrition, 2025)
BackgroundThe relationship between the gut microbiota and infertility has garnered increasing attention. However, the associations between dietary index for gut microbiota (DI-GM), an indicator of microbial diversity, and infertility remain insufficiently explored.MethodsWe analyzed data from 3,058 participants in the NHANES 2013–2020 cycles, employing weighted generalized linear models and smooth curve analyses to examine their associations. Mediation analysis was conducted to assess the role of body mass index (BMI).ResultsAfter adjusting for confounding factors, a higher DI-GM score was significantly associated with a lower prevalence of infertility (OR = 0.89, 95% CI = 0.81–0.98, p = 0.029). Compared with individuals with a DI-GM score of 0–3, those with a score ≥6 presented a significantly lower prevalence of infertility (OR = 0.64, 95% CI = 0.43–0.96, p = 0.039). BMI mediated 5.98% of the association between DI-GM and infertility.ConclusionA higher DI-GM score is associated with a lower prevalence of infertility. Future studies should employ longitudinal designs to validate these findings.